A multicriteria approach based on fuzzy QFD for choosing criteria for supplier selection. (November 2016) - Lima-Junior, Francisco Rodrigues; Carpinetti, Luiz Cesar Ribeiro
Graphical abstract: Highlights: Proposes a method to aid the choice and weighting of criteria to supplier selection. Combines fuzzy QFD with a classification procedure based on a two dimensional grid. Assesses the difficulty to get data to evaluate the suppliers on each criterion. The type of item is considered to define of the list of requirements and criteria. The method classifies the criteria into groups so as to guide the final selection. Abstract: This paper proposes a new multicriteria decision making method to aid the choice and weighting of criteria to be used in the supplier selection process. The method combines the fuzzy QFD technique for weighting the criteria with a procedure for assessing the difficulty to obtain information to evaluate the suppliers on each criterion. The choice and weighting of the criteria derive from a systematic procedure based on the use of linguistic terms to judge the importance of the related requirements and the intensity of the relationship between requirements and criteria. In the final step, the proposed method classifies the criteria into four groups (priority, critical, complementary and costly) so as to guide the final choice of criteria. The method was implemented in Excel and applied to a pilot case in an automotive company, which classified the criteria into groups so as to guide the decision in the final selection. Competitive price, delivery in full on time, product conformance and quality certification were categorized into the priority group meaning that they should be used in the supplier selection process. On the other hand, commitment to cost reduction, financial situation, responsiveness to demand change, commitment to quality improvement and potential for collaboration were classified as critical, meaning that they are important but they require a bigger effort of data collection. The results of the application were considered by the decision makers as consistent and aligned with the strategic competitive priorities of the supply chain. Differently from other studies, the type of item as well as the type of supply chain was formally considered in the determination of the initial list of requirements and criteria. Moreover, final selection of the set of criteria is also dependent on the linguistic evaluation of the degree of difficulty of data collection.